Analysis of knowledge, attitudes, and practices related to antibiotics and antimicrobial resistance awareness among community members in Ghana and Burkina Faso - Cama i Gibernau, Elisenda; Aglanu, Leslie Mawuli; Zakane, Alphonse; Dekker, Denise; Jahn, Albrecht; Sié, Ali; Amuasi, John Humphrey; Souares-Coutant, Aurélia (Antimicrobial resistance and infection control, 2025)
Antimicrobial resistance (AMR) is a global health concern, particularly in low- and middle-income countries. As human behaviour plays a crucial role in the emergence and spread of resistance, data on the understanding of AMR awareness are very important for assessing the situation and developing effective interventions. The aim of this study was to analyse the knowledge, attitudes and practices (KAP) related to antibiotics and awareness towards antibiotic resistance among community members in two districts in Ghana, and Burkina Faso.